EVALUASI KEKUATAN SAMBUNGAN PADA BANGUNAN UTAMA MASJID AGUNG KRATON SURAKARTA - Susilo, Rima Wahyu; Awaludin, Ali; Irawati, Inggar Septhia (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2023)
Masjid Agung Kraton Surakarta is located in the city of Surakarta, Central Java Province and is a National Cultural Heritage building. The mosque was built during the reign of Pakubuwana II in 1745 AD with a total area of 19,180 m2. The main building of the mosque measures 34.2 meters x 33.5 meters. The mosque is supported by 4 main pillars (Soko Guru) and 12 additional pillars (Soko Rawa) made of wood. Indonesia is located at the confluence of three major world plates that cause the Pacific earthquake line and the Asian earthquake line. This causes the probability of large earthquake waves, and the frequency of occurrence is quite frequent in Indonesia. According to SNI 1726-2019, houses of worship have a risk category 4, where the building must maintain the function of the building structure during an earthquake. One of the regulations for evaluating a building is SNI 1726-2019. In this study, a tenant mortise joint with a maximum moment of 7.2 kNm and a rotation of 0.124 rad was modeled on the main structure of the Surakarta Grand Kraton Mosque with SAP2000 software. The loading combination is based on SNI 1726 2019 with earthquake loads obtained from the rsa cipta karya site. Based on the structural analysis that has been carried out, the results show that the maximum moment that occurs in the connection is 0.5373 kNm which is located at joint 89 elements 161 and obtained a maximum deformation of 6.442 mm.